2016
DOI: 10.1007/s00420-016-1176-9
|View full text |Cite
|
Sign up to set email alerts
|

Emotional dissonance and sickness absence: a prospective study of employees working with clients

Abstract: Emotional dissonance is a risk factor for the presence of medically certified sickness absence in client-driven work environments. Theoretical models of sickness absence, as well as interventions aiming to prevent sickness absence in such environments, should be aware of the effect emotional dissonance may have on employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…Role conflict is generally considered to be a risk factor for illhealth [25]. The current findings support this notion (Table 2) and are in line with previous studies [24,30,31]. However, effects of exposure to a workplace terrorist attack on subsequent sickness absence seems to be more pronounced with lower levels of role conflict than higher.…”
Section: Under Review) a Valid Basis For Comparison Of Results Is Cusupporting
confidence: 91%
“…Role conflict is generally considered to be a risk factor for illhealth [25]. The current findings support this notion (Table 2) and are in line with previous studies [24,30,31]. However, effects of exposure to a workplace terrorist attack on subsequent sickness absence seems to be more pronounced with lower levels of role conflict than higher.…”
Section: Under Review) a Valid Basis For Comparison Of Results Is Cusupporting
confidence: 91%
“…While physical work conditions are the most likely explanations for the socioeconomic gradient in LTSA (Christensen et al 2008;Löve et al 2013), also psychosocial factors are pertinent (Melchior et al 2005;Niedhammer et al 2008). Similarly, certain physical and psychosocial hazards have also been linked to heightened risk of LTSA for caring work (Aagestad et al 2016) and researchers have particularly emphasized the emotional demands as straining (Indregard et al 2017;Rugulies et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Research on burnout has found that caring work results in stress and exhaustion (Barron & West 2007;Wieclaw et al 2006), and burnout is associated with sickness absence (Ahola et al 2008;Borritz et al 2010). Emotional labor is also associated with sickness absence, both in the general working population Lund et al 2006) and in human service work (Indregard et al 2017;Rugulies et al, 2007). In addition to the psychosocial factors associated with burnout and emotional labor, threats of violence and actual violence (Aagestad, Tyssen, et al 2014;Michélsen et al 2014;Rugulies et al 2007) as well as physical strain (Andersen et al 2012) have been found to predict sickness absence among workers caring for clients.…”
Section: Previous Research On Predictors Of Ltsa and Hypothesesmentioning
confidence: 99%
“…However, they have been different clarifications on what it means to be in a particular mood or emotional state. For instance, being in a particular mood can be explained by generalised affective states (Indregard, Knardahl & Nielsen, 2016). Precisely, while the constellation of factors may be present to influence an individual mood, the mood itself is not fixed on any exact object (Fernández-Berrocal, Gutiérrez-Cobo, Rodriguez-Corrales & Cabello, 2017).…”
Section: Affective Well-being and Absenteeism Discoursementioning
confidence: 99%